Standardizing Purish Jala Nimajjan Pariksha And Salivary Ph For Ajeerna Diagnosis: A Pilot Study.. - Tengse, Vaishnavi; Pande, Sumant (Journal of Neonatal Surgery, 2025)
Background: Ajeerna (Indigestion) is a common digestive disorder caused by an imbalance in the digestive fire (Agni) and the accumulation of Ama (toxins). Diagnosis of Ajeerna is primarily based on subjective symptoms in Ayurvedic practice, but there is a need for objective, standardized diagnostic methods. This study aims to assess the feasibility of using salivary pH and Purish Jala Nimajjan Pariksha (a traditional Ayurvedic test) as objective diagnostic tools for Ajeerna. Methods: A pilot study was conducted with 12 patients from each of the three subtypes of Ajeerna: Aamajeerna (Kapha predominant), Vidagdhajeerna (Pitta predominant), and Vishtabdhajeerna (Vata predominant). Salivary pH was measured using a pH meter, and stool behavior was observed using the Purish Jala Nimajjan Pariksha test. Stool samples were assessed for sinking (indicating Ama) or floating (indicating normal digestion). The results were compared between groups, and statistical analysis was conducted to evaluate the correlation between salivary pH and stool behavior. Results: The Aamajeerna group showed the lowest salivary pH (5.9) and the highest proportion of sinking stools (11 out of 12), indicating a high presence of Ama. The Vidagdhajeerna group had moderate salivary pH (6.5) and a mixed pattern of sinking and floating stools. The Vishtabdhajeerna group exhibited the highest pH (7.1) and the majority of floating stools (9 out of 12), suggesting better digestion and less Ama. Conclusion: Salivary pH and Purish Jala Nimajjan Pariksha provide valuable complementary diagnostic tools for assessing digestive dysfunction in Ajeerna. Standardizing these methods could enhance diagnostic accuracy and contribute to more personalized treatment strategies in both Ayurvedic and modern clinical settings